3‐D graphene‐supported mesoporous SiO2@Fe3O4 composites for the analysis of pesticides in aqueous samples by magnetic solid‐phase extraction with high‐performance liquid chromatography. Issue 9 (5th April 2016) - Wang, Xuemei; Wang, Huan; Lu, Muxin; Ma, Xiaomin; Huang, Pengfei; Lu, Xiaoquan; Du, Xinzhen
Abstract : Three‐dimensional graphene‐supported mesoporous silica@Fe3 O4 composites (mSiO2 @Fe3 O4 ‐G) were prepared by modifying mesoporous SiO2 ‐coated Fe3 O4 onto hydrophobic graphene nanosheets through a simple adsorption co‐condensation method. The obtained composites possess unique properties of large surface area (332.9 m 2 /g), pore volume (0.68 cm 3 /g), highly open pore structure with uniform pore size (31.1 nm), as well as good magnetic separation properties. The adsorbent (mSiO2 @Fe3 O4 ‐G) was used for the magnetic solid‐phase extraction of seven pesticides with benzene rings in different aqueous samples before high‐performance liquid chromatography. The main parameters affecting the extraction such as adsorbent amount, volume of elution solvent, time of extraction and desorption, salt effect, oscillation rate were investigated. Under the optimal conditions, this method provided low limits of detection (S/N = 3, 0.525–3.30 μg/L) and good linearity (5.0–1000 μg/L, R 2 > 0.9954). Method validation proved the feasibility of the developed adsorbent, which has a high extraction efficiency and excellent enhancement performance for pesticides in this study. The proposed method was successfully applied to real aqueous samples, and satisfactory recoveries ranging from 77.5 to 113.6% with relative standard deviations within 9.7% were obtained.